AN ANALYSIS OF ERROR IN CONVERSATION OF THE SECOND GRADE STUDENTS OF ST. FAMILIA JUNIOR HIGH SCHOOL KUPANG IN ACADEMIC YEAR 2018/2019 - Erlinda Sonya Pale (Academic Journal of Educational Sciences, 2020)
This study is entitled “An Analysis of Error in Junior High School Students’ Conversation. It aims at answering the followingquestions (1) what are the errors in junior high school students’ conversation? (2) How many frequencies of those errors?. The method applied inthis study was descriptive qualitative method. The study was conducted at St. Familia Junior high school Sikumana, Kupang – East NusaTenggara. The method applied in this study was descriptive qualitative method. The subjects of the study were the second year students of St.Familia junior high school. In collecting the data, the researcher provided some topics chosen by the students to create a simple conversation.Smart phone was the instrument used to obtain the data. The result of the study shows that (1) Errors in students’ conversation consist of sometypes and the total frequency of error is 29. (2) The total frequency of misformation errors is 10; 3 errors made by pair one, 2 errors made by pairfour, 1 error made by pair five 2 errors made by pair six and the last two errors were made by pair seven and eight (3) The total frequency ofaddition errors is 5; 2 errors made by pair three, and the last 3 errors were made by pair four, six, and seven. (4) The total frequency ofmisordering errors is 3, made by pair four, five and six (4) Most of the students made omission errors, with the frequency of errors is 11; 5 errorsmade by pair one, 2 errors made by pair two, 2 errors made by pair seven, and the last 2 errors were made by pair six and eight (6) Most of thestudents omitted to be ”is” (7) The errors made by the students did not influence the flow of the conversation (8) Those errors are not significantsince the students only made 36,25% of errors from the total sentences they produced (80 sentences). Based on the result above, the researchersuggest (1) The students should learn on how to make a conversation focusing on grammar, especially on the omission and misformationbecause more errors occurred in these two types (2) The teacher of English in the school need to pay more attention to the students’ grammarwhen teaching.